Conditions of development of rural territories: Russian and foreign experience - Yarkova, T.M. (2019)
Currently, the issues of sustainable development of rural territories for Russia have gained particular relevance. Meanwhile, these issues have been given due attention over the years. The current Russian system of program-targeted management of rural development does not have a ubiquitous effect, although it has definitely positive results. This is evidenced by sociological surveys of villagers, who in most cases note the invariability of the socio-economic situation. Foreign experience in the development of agriculture and rural areas has led to the need to use the principles of ecological agriculture with the practical production of organic products, which allows us to successfully solve social and economic problems. At the same time, the experience of using Foresight projects with a well-known implementation algorithm, which has gained its relevance in Russia recently, has long been positively recommended abroad. Given the many identified problems in managing the development of rural territories in Russia, it is important to use elements of foreign experience and to carry out immediate work to improve the current program-target approach.